Entrepreneurial education learning style among university students - Noraani Mustapha; Ong Soon Chuan; Wan Mohd Yusuff Wan Ibrahim (Faculty of Entrepreneurship and Business,UMK, 2015)
The purpose of teaching entrepreneurship is to give the students an exposure towards a better understanding of the concept of entrepreneurship; and to nurture interest and awareness in business and to help them discover possibilities of various opportunities in the business world. Thus the pedagogy as well as students’ learning style needs to be adjusted based on a broadening market interest in entrepreneurial education. Moreover many studies have shown that academic performance of university students is related to their learning styles. The objectives of this study were to examine the differences of learning style between male and female students, to determine the differences in learning style between technical and non-technical students and to ascertain the most prominence learning style among university students. By means of cluster random sampling data was collected from 997 students from five public universities in East Coast and Southern region of Peninsula Malaysia. For this study the Grasha-Riechmann Student Learning Style Scales (GRSLSS) was utilized to identify student learning preferences in six learning style categories: avoidant, participative, competitive, collaborative, dependent and independent. By using self- administered questionnaire of 60-item scales data were collected and responses were recorded using a 5-point Likert scale; ranges from 1 (strongly disagree) through 5 (strongly agree). The findings indicated that female students had higher tendency in collaborating with female colleagues and participating cooperatively in their activities. Female students obtained significantly higher mean in collaborative, participative, and dependent styles than males, whereas in avoidant, and independent styles, the mean for males were higher than the opposite gender. The findings also indicated that the technical group’s mean in avoidant and competitive were higher than non-technical group whereas mean for collaborative, participative, dependent, and participative styles were higher among non- technical than those of the technical group. In general there was no significant difference in terms of learning style preferred either by male or female and by technical and non-technical students